Long-Term Fracture Resistance of Simulated Immature Teeth Filled with Various Calcium Silicate-Based Materials. (13th June 2016) - Guven, Yeliz; Tuna, Elif Bahar; Dincol, M. Emir; Ozel, Emre; Yilmaz, Bulent; Aktoren, Oya
Abstract : Objective . The aim of this in vitro study was to evaluate the long-term fracture resistance of simulated human immature permanent teeth filled with BioAggregate ™ (BA), mineral trioxide aggregate (MTA), and EndoSequence® Root Repair Material (ERRM). Material and Methods . 40 teeth, simulated to average root length of 13 ± 1  mm (Cvek's stage 3), were included in the study. The teeth were randomly divided into four groups: Group 1: DiaRoot ® BA, Group 2: MTA-Plus ™ (MTA-P), Group 3: MTA-Angelus (MTA-A), and Group 4: ERRM. The root canal filling materials were applied according to the manufacturers' instructions. After 24 months of incubation, the roots of the teeth were embedded in acrylic blocks and subjected to fracture testing. The resultant data were analyzed statistically by Kruskal-Wallis and Mann-Whitney U tests. Results . Mean (±SD) failure loads (MPa) were 20.46 ± 2.53 for BA, 18.88 ± 5.13 for MTA-P, 14.12 ± 1.99 for MTA-A, and 17.65 ± 4.28 for ERRM groups. BA group exhibited the highest and MTA-A group showed the lowest resistance to fracture. Significant differences in fracture resistance were found between the groups of BA and MTA-A (p < 0.001 ), MTA-P and MTA-A (p < 0.05 ), and ERRM and MTA-A (p < 0.05 ). Conclusion . Within the limitations of this study, data suggests that BA-filled immature teeth demonstrate higher fracture resistance than other groups at 24 months appearing to be the most promising material tested.